Social media and communication technology in education: A Literature review - Manu, Gerlan Apriandy (Univeritas Papua, 2023)
This article aims to examine the impact of the use of social media and communication technologies in the context of education in the digital age. Utilizing a literature review as its primary method, the study collects and analyzes data from various prior studies using the PRISMA 2020 methodology. The analysis technique involves comparing research findings and integrating insights from diverse academic sources to gain a comprehensive understanding of the research topic. The results reveal that social media and communication technology enhance student engagement and motivation in learning. Additionally, the use of social media and communication technology in education demonstrates varied effects on students' learning motivation and poses potential risks to their mental well-being. These findings provide crucial insights for educators and policymakers in effectively and safely integrating digital technology into education.